Strategi Pengembangan Situs Pariwisata Pantai Natsepa, Desa Suli Kabupaten Maluku Tengah (Natsepa Beach Tourist Site Development Strategy Suli Village, Maluku Tengah Regency) - Payapo, Wilda R.; Effendi, Jani (Universitas Brawijaya, Indonesia, 2009)
The research aims to (1) to describe factors that influence the frequencies of visit in Natsepa Beach Tourist Site in Suli Village in Maluku Tengah Regency; (2) to understand the development strategy of Natsepa Beach Tourist Site in Suli Village in Maluku Tengah Regency. The population of the research was all the visitors of the tourist site that consisted of 4,341 people monthly. Sample was determined by accidental sampling namely 93 visitors who were found in sites. Data analysis was done descriptive quantitative qualitative through : Multiple Regression Analysis and SWOT analysis. The result of the research indicated that; (1) from the seven assumed influence factors, evidently income, travel cost, time of visiting, age and site attraction influenced significantly toward the visitation to bathing site. While, work occupation and education were insignificantly influence because the visitation to the tourist site in based on the distance that was relatively short with cheap travel cost; based on SWOT analysis, the strategy that can be done in developing Tourist Site : (1) development of tourism object compatible with the Government Policy and the Tourism Master Plan; (2) improvement of access to tourism site; (3) increase tourism promotion; (4) development of tourism facility and its supporting element; (5) provide public transportation to the site; (6) increase the quality of professional staffs in tourism activity; (7) increase the quality of tourist program package; (8) increase security toward public nuisance; (9) implementation of sanction to tourist site disturber; ang (10) transfer of management of tourist site to the private sectors.Keywords: tourist site, development strategy, SWOT analysis.